2013
DOI: 10.1074/jbc.m112.414235
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Scrambling Describes the Oligomer Formation of Superoxide Dismutase (SOD1) Proteins in the Familial Form of Amyotrophic Lateral Sclerosis

Abstract: Background: Cu,Zn-superoxide dismutase (SOD1) possesses a highly conserved intramolecular disulfide bond. Results: Structural destabilization of SOD1 scrambles the intramolecular disulfide to form cross-linked oligomers with an intermolecular disulfide bond. Conclusion: Disulfide scrambling is a key to understand the folding/misfolding process of SOD1. Significance: A disulfide-scrambling model provides a molecular pathomechanism describing the formation of disulfide-linked SOD1 oligomers in amyotrophic latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 32 publications
4
63
0
Order By: Relevance
“…We found that disulfides between cysteines close together in sequence, particularly Cys32 and Cys41, stabilized a partially unfolded intermediate state prone to specific intermolecular interactions. It is worth noting that disulfide bonding is critical to the aggregation pathways of other wellknown disease-related proteins, including superoxide dismutase 1 and β2-microglobulin (34,35,37,38). Conversely, disulfide engineering has been used to trap important folding intermediates in a variety of proteins (71).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that disulfides between cysteines close together in sequence, particularly Cys32 and Cys41, stabilized a partially unfolded intermediate state prone to specific intermolecular interactions. It is worth noting that disulfide bonding is critical to the aggregation pathways of other wellknown disease-related proteins, including superoxide dismutase 1 and β2-microglobulin (34,35,37,38). Conversely, disulfide engineering has been used to trap important folding intermediates in a variety of proteins (71).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, some pathways of protein aggregation depend strongly on the redox environment. Notable examples include superoxide dismutase 1 (34,35) and β2-microglobulin (36)(37)(38). We and others have demonstrated that γ-crystallins, too, form crucial disulfide-mediated interactions.…”
mentioning
confidence: 99%
“…These oligomers are thought to be responsible for the toxic gain of function, similar to what has been proposed for other neurodegenerative diseases [24][25][26][27] . Generation of soluble oligomers was found to occur through oxidation of the two free cysteines of SOD1 (C6 and C111) 28,29 , as well as through other possible mechanisms 30,31 , which give rise to various aggregation products 32,33 , including amyloid-like structures 34,35 .…”
mentioning
confidence: 99%
“…Thiol/disulfide exchange reactions involving disulfide 57-146 and the free cysteines of hSOD1 have been proposed to contribute to aggregation and misfolding in ALS (15,16,26,(37)(38)(39). However, description of these reactions at the molecular level is still missing.…”
Section: Disulfide 57-146 Is Buried In the Folded State Of Hsod1-mentioning
confidence: 99%
“…Non-native disulfide formation contributes to form and/or stabilize SOD1 aggregates that accompany progression of the disease (12)(13)(14)(15). Indeed, it has been suggested that scrambling of the disulfide and the free cysteines in SOD1 results in formation of insoluble aggregates (16). Interestingly, the free cysteines in SOD1, in particular Cys-111, contribute to the toxicity of mutant forms of SOD1 (14,17).…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%